Resistance of Klebsiella pneumoniae Strains Carrying blaNDM–1 Gene and the Genetic Environment of blaNDM–1 - Xiang, Tianxin; Chen, Chuanhui; Wen, Jiangxiong; Liu, Yang; Zhang, Qi; Cheng, Na; Wu, Xiaoping; Zhang, Wei (Frontiers in Microbiology, 2020)
Objective Regional dissemination is the major cause of the widespread prevalence of a plasmid-encoding NDM-1 enzyme. We here investigated the drug resistance, joint efficiency, and gene environment of a Klebsiella pneumoniae strain carrying blaNDM-1. Materials and Methods Carbapenem-insensitive strains were analyzed using the VITEK 2 Compact. Strains carrying blaNDM-1 were identified by polymerase chain reaction and sequencing. Antimicrobial susceptibility testing and plasmid conjugation experiment was then conducted. Strains carrying blaNDM-1 were subjected to Southern blot analysis. After gene mapping of blaNDM-1, library construction and sequencing, plasmids were subsequently spliced and genotyped using the Glimmer 3.0 software and then analyzed by Mauve software. Results Among 1735 carbapenem-insensitive strains, 54 strains of blaNDM-1-positive bacteria were identified, which consist of 44 strains of K. pneumoniae, 8 strains of Acinetobacter baumannii and 2 strains of Escherichia coli. Strains carrying blaNDM-1 had a resistance rate of more than 50% in most antibiotics. Plasmid conjugation between strains carrying blaNDM-1 and E. coli strain J53 had a success rate of 50%. Southern blot analysis indicated that every strain had multiple plasmids containing blaNDM-1. Among the 5 plasmids containing blaNDM-1in K. pneumonia for sequencing, 2 plasmids with complete sequences were obtained. And we found: (i) The p11106 and p12 plasmids were highly similar to pNDM-BTR; (ii) The p11106 and p12 plasmids showed differences in the 20-30 kb region (orf00032-orf00043) from the other six plasmids; and (iii) blaNDM-1 was located in the middle of the orf00032-orf00043 region, where as ble was found nearby. Two tnpA genes were on the top, and orf00052 (tnpA) in the 36kb region was in the downstream sequence. Conclusions A blaNDM-1-containing bacterium exhibits multidrug resistance, which is rapidly spread and transferred by efficient plasmid conjugation. The presence of ble and tnpA suggests that blaNDM-1 originates from A. baumannii, which is retained in K. pneumonia over a long period by transposition of mobile elements. These findings need to be verified by future research.